2009
DOI: 10.1007/s00442-009-1317-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrologic attributes on brown trout recruitment in low-latitude range margins

Abstract: Factors controlling brown trout Salmo trutta recruitment in Mediterranean areas are largely unknown, despite the relevance this may have for fisheries management. The effect of hydrological variability on survival of young brown trout was studied during seven consecutive years in five resident populations from the southern range of the species distribution. Recruit density at the end of summer varied markedly among year-classes and rivers during the study period. Previous work showed that egg density the previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 62 publications
3
46
2
Order By: Relevance
“…Water temperature had a higher impact on the length of age-0 trout when compared with older trout. Incubation temperature could have influenced the date of emergence from the stream bed and may have caused interpopulation differences in emergence time (Elliott and Hurley 1998;Ojanguren and Braña 2003;Nicola et al 2009), which would lead to variations in the length of trout after the first growing period (Ojanguren and Braña 2003;Nicola and Almodóvar 2004). Water temperature may also influence the physiology of fish, causing differences in enzymes related to food conversion efficiency (Rungruangsak-Torrissen et al 1998) as discussed by Jonsson et al (2005) for Atlantic salmon.…”
Section: Discussionmentioning
confidence: 97%
“…Water temperature had a higher impact on the length of age-0 trout when compared with older trout. Incubation temperature could have influenced the date of emergence from the stream bed and may have caused interpopulation differences in emergence time (Elliott and Hurley 1998;Ojanguren and Braña 2003;Nicola et al 2009), which would lead to variations in the length of trout after the first growing period (Ojanguren and Braña 2003;Nicola and Almodóvar 2004). Water temperature may also influence the physiology of fish, causing differences in enzymes related to food conversion efficiency (Rungruangsak-Torrissen et al 1998) as discussed by Jonsson et al (2005) for Atlantic salmon.…”
Section: Discussionmentioning
confidence: 97%
“…Strong flow events during emergence depressed summer recruitment. Such disturbance events drastically reduce the quantity and quality of suitable physical habitat, which results in high YOY mortality through both direct downstream displacement of subordinate individuals without shelter (e.g., [52]) and delayed carry-over effects on individuals occupying low-quality habitats that affect their performance in the following season (see [53]). We also observed that juvenile physical habitat can limit subsequent adult abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effects of fish on invertebrates should be strongest in streams with high densities of fish and low densities of invertebrates (Reice 1991). In the study streams fish species are currently exploited by angling (Nicola et al 2009) and probably populations do not reach densities high enough to control benthic communities.…”
Section: Discussionmentioning
confidence: 99%